Different Effects of Strong-Bonded Water with Different Degrees of Substitution of Sodium Sulfobutylether-β-cyclodextrin on Encapsulation - Xiaofeng Wang; Jiaqi Huang; Dengchen Yang; Ting Huang; Yang Yang; Jiasheng Tu; Jian Zou; Huimin Sun; Xia Zhao; Rui Yang (MDPI AG, 2024)
The encapsulation of sodium sulfobutylether-β-cyclodextrin (SBE-β-CD) is influenced not only by the degree of substitution (DS) but also by the presence of strong-bonded water (SBW). Guests compete with SBW for positions within the cavity of SBE-β-CD. However, the correlation between DS and SBW was not clear. This study revealed a positive correlation between DS and SBW utilizing Karl Fischer titration. The mechanism may be attributed to molecular polarizability. To explore the impact of SBW inside SBE-β-CD with different DS on encapsulation, density functional theory was employed. Throughout the release process, an increase in enthalpy is unfavorable, while an increase in entropy favors spontaneous reaction occurrence. For SBE-β-CD (DS = 2, 3), enthalpy increase is the primary factor, leading to the retention of SBW within the cavities and consequently hindering guest entry. In contrast, for SBE-β-CD (DS = 4, 7), the situation differs. For SBE10-β-CD, the influence of SBW is minimal. This study aims to elucidate the relationship between DS and SBW, as well as the effect of SBW inside SBE-β-CD with different DS on encapsulation. It is crucial for a comprehensive understanding of the factors affecting the encapsulation of SBE-β-CD, thereby promoting quality control and functional development of SBE-β-CD.